Diagnostic Accuracy and Efficacy of Shear-Wave Elastography for Evaluation of Solid Breast Masses - Sahu, Niranjan; Agrahari, Ashish Kumar; Parida, Bikash; Das, Somadatta (Medical Science: Trends and Innovations Vol. 12, 2025)
Background: Breast Carcinoma is one of the most common malignancies globally, especially in patients aged 50-55. However, in India, Breast Carcinoma is more prevalent among younger women. Although various imaging modalities are available for evaluating suspicious breast lesions, ultrasound-based Shear-Wave Elastography (SWE) is an advanced, non-invasive technique complementary to grayscale sonography. Shear wave elastography is sensitive to identifying subtle changes in tissue architecture. This technique evaluates the elasticity of a specific tissue by applying sonic pressure to that tissue. The elasticity of the lesion is measured using the ultrasound elastography color scale. Objective: The aim is to assess the role of SWE in evaluating solid breast masses in correlation to histopathological examination (HPE) study results. Subjects and Methods: This prospective study was done in a tertiary care teaching hospital. A study population of 50 women aged 18 years or above with an ultrasonographic diagnosis of solid breast masses was included. A standard proforma was used to collect data in the included study group. The proforma also included a general checkup and a local assessment of the patient’s breast lump by inspection and palpation. In all cases, quantitative elasticity values were measured using two 2 mm-diameter circular quantification ROIs (region-of-interest). Statistical Package for Social Sciences (SPSS) 20.0 was used for statistical analyses. An independent two-sample t-test was performed to compare continuous variables between the benign and malignant groups. Results: SWE is utilized to differentiate malignant from benign breast tumors. A significantly higher value of SWE’s elasticity ratio (E-ratio) was observed in malignant tumors than in benign tumors (p <0.0001). The area-under-curve (AUC) for the Breast Imaging Reporting & Data System (BI-RADS 4) lesions was 0.522 [95% confidence interval (CI), 0.343-0.701] with an E-ratio cut-off score of 85.25, the sensitivity and specificity were 50% for diagnosing malignant tumors, whereas AUC for the HPE study was 1.000 (95% CI, 1.000-1.000) with an E-ratio cut-off score of 134.25; both the sensitivity and specificity were 100% for diagnosing malignant tumors. Conclusions: A well-defined SWE E-ratio range might help differentiate malignant from benign breast tumors and predict their aggressiveness. Furthermore, SWE’s correlation with BI-RADS in suspicious lesions adds to HPE's advantage in distinguishing malignant tumors from benign ones. More research with large sample sizes is required in the near future to emphasize the SWE findings more accurately.